The Influence of Problem Based Learning Models on the Learning Outcomes of Students of Grade III of State Elementary School 002 Sintong - Julia Lingga , Leny; Fitriyani, Nofira (Newinera Publisher, 2025)
This study was prompted by the low learning outcomes of third-grade students at SD Negeri 002 Sintong, particularly in Science (IPA), due to conventional teaching methods that inadequately engage students. Innovation in learning models, such as Problem Based Learning (PBL), is crucial for enhancing the quality of basic education and motivating students. The objective of this research was to analyze the effect of the PBL model on the learning outcomes of third-grade students at SD Negeri 002 Sintong. This research adopted a quantitative approach with a quasi-experimental design, specifically the Nonequivalent Control Group Design. The population comprised all 64 third-grade students at SD Negeri 002 Sintong. The entire population of 64 students was also selected as the research sample using a purposive sampling technique. The sample was divided into two groups: 32 students in the experimental group, who received PBL instruction, and 32 students in the control group, who received conventional instruction. Data were collected through pretests and posttests using cognitive learning outcome instruments that had been validated and tested for reliability. Data analysis involved normality (Shapiro- Wilk) and homogeneity (Levene's Test) pre-requisite tests, followed by an Independent Sample T-Test. The results indicated that the data were normally distributed and homogeneous, satisfying the statistical assumptions. The Independent Sample T- Test revealed a significant difference in student learning outcomes between the experimental and control groups, with a t- value of 24.1716 and a p-value of 0.000 (p < 0.05).